Dialogare: compendio di logica - BRUNI, Riccardo (Strumenti per la didattica e la ricerca, 2017)
"Logic", as understood in this volume, is the set of knowledge at the basis of man's reasoning faculties: understanding, analysing, arguing. The text presents a review of topics which are useful to strengthen the skills related to reasoning faculties through a brief introduction to the theoretical aspects and exercises intended to assess the understanding. The volume is divided into parts, which are organised in teaching units. The parts and units are presented in such a way that, following the thread in the order in which they are proposed, we move from one topic to the next, acquiring the prerequisites necessary for to what comes after. The text therefore lends itself to a "systematic" use, aimed at an extensive study. However, nothing prevents the reader from adapting the material to other needs, choosing only a few topics that they consider useful to integrate their knowledge, to do a "review" or to further practice on already known topics.